Can the Protection of Goods of Common Interest be a Justification for Interventions in State Sovereignty? - Possibility of an 'Ecological' Intervention - Baenke, Janet (Centre for Law and Society, 2026)
To begin with: humankind depends essentially on a functional eco-system. For instance, without clean air, clean water or an intact ozone layer, only a few examples, is life on earth not possible. That means that the protection of the environment is indirectly the protection of humanity as well.